A Valuable Publication - Gasparyan, Seda (Armenian Folia Anglistika, 2015)
Much More than Metaphor Master Tropes of Artistic Language and Imagination Elzbieta Chrzanowska-Kluczewska Frankfurt am Main: Peter Lang, 2013, 196 pp.